2022
DOI: 10.1002/ecs2.4160
|View full text |Cite
|
Sign up to set email alerts
|

Riverscape heterogeneity in estimated Chinook Salmon emergence phenology and implications for size and growth

Abstract: Many salmonid‐bearing rivers exhibit thermal and hydrologic heterogeneity at multiple spatial and temporal scales, but how this translates into spatiotemporal patterns of fry emergence is poorly understood. Understanding this variability is important because emergence timing determines the biophysical conditions fish first experience (e.g., temperature, flow, and food supply), thereby influencing growth opportunities and survival during this critical life stage. We predicted spring Chinook Salmon (Oncorhynchus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For example, differences in phenology should spread the risk of exposure to episodic events such as floods, droughts or heatwaves, thereby reducing the likelihood of synchronous declines in survival and growth across populations (Kaylor et al., 2021; Kovach et al., 2016). Additionally, effects of temperature on growth differed considerably among streams with similar thermal regimes, adding another layer of variation that may help to stabilise productivity through portfolio effects (Kaylor et al., 2022; Lisi et al., 2013). Improved understanding of fine‐scale population and habitat diversity across the species range could provide insights into the resilience of brook trout and the ecosystem services they provide (e.g., supporting fisheries and acting as apex predators in small streams).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, differences in phenology should spread the risk of exposure to episodic events such as floods, droughts or heatwaves, thereby reducing the likelihood of synchronous declines in survival and growth across populations (Kaylor et al., 2021; Kovach et al., 2016). Additionally, effects of temperature on growth differed considerably among streams with similar thermal regimes, adding another layer of variation that may help to stabilise productivity through portfolio effects (Kaylor et al., 2022; Lisi et al., 2013). Improved understanding of fine‐scale population and habitat diversity across the species range could provide insights into the resilience of brook trout and the ecosystem services they provide (e.g., supporting fisheries and acting as apex predators in small streams).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while the timing of hatch and emergence shifted earlier in every stream, groundwater-dominated streams exhibited slower phenological shifts, perhaps reflecting their more stable temperatures overall (Figure 4). Similar variation in hatch and emergence times in Chinook salmon can mediate spatial patterns in growth (Kaylor et al, 2021(Kaylor et al, , 2022, but the consequences of the disparate phenologies observed among Cape Race brook trout populations are currently less clear (see below). Moreover, reproductive timing was not accounted for when reconstructing degree-day accumulations, as spawning ground surveys (see Fraser et al, 2019) indicate that brook trout reproduce at least 1-2 weeks later in groundwater-dominated streams.…”
Section: Phenology and Growth Under Climate Changementioning
confidence: 99%
“…Observed patterns in juvenile Chinook salmon out-migration timing and sizes at these traps provide an opportunity to test hypotheses about, and advance our understanding of, juvenile Chinook salmon early life history (e.g., Zimmerman et al, 2015). However, these patterns are the product of multiple processes including spawn timing and location, egg incubation, movement, survival, and growth, all of which are regulated by temperature (Kaylor et al, 2021;Kaylor et al, 2022). Therefore, interpreting patterns in out-migrant timing and sizes requires combining our understanding of these biological processes along with spatially and temporally explicit estimates of water temperature upstream of the traps.…”
Section: Introductionmentioning
confidence: 99%